The Principal Forces of Oocyte Polarity Are Evolutionary Conserved but May Not Affect the Contribution of the First Two Blastomeres to the Blastocyst Development in Mammals - Hosseini, Sayyed-Morteza (PLoS One, 2016)
Oocyte polarity and embryonic patterning are well-established features of development in lower species. Whether a similar form of pre-patterning exists in mammals is currently under hot debate in mice. This study investigated this issue for the first time in ovine as a large mammal model. Microsurgical trisection of unfertilized MII-oocytes revealed that cortical cytoplasm around spindle (S) contained significant amounts of total maternal mRNAs and proteins compared to matched cytoplast hemispheres that were located either near (NS) or far (FS) -to-spindle. RT-qPCR provided striking examples of maternal mRNA localized to subcellular substructures S (NPM2, GMNN, H19, PCAF, DNMT3A, DNMT1, and STELLA), NS (SOX2, NANOG, POU5F1, and TET1), and FS (GCN) of MII oocyte. Immunoblotting revealed that specific maternal proteins DNMT3A and NANOG were asymmetrically enriched in MII-spindle-half of the oocytes. Topological analysis of sperm entry point (SEP) revealed that sperm preferentially entered via the MII-spindle-half of the oocytes. Even though, the topological position of first cleavage plane with regard to SEP was quite stochastic. Spatial comparison of lipid content revealed symmetrical distribution of lipids between 2-cell blastomeres. Lineage tracing using Dil, a fluorescent dye, revealed that while the progeny of leading blastomere of 2-cell embryos contributed to more cells in the developed blastocysts compared to lagging counterpart, the contributions of leading and lagging blastomeres to the embryonic-abembryonic parts of the developed blastocysts were almost unbiased. And finally, separated sister blastomeres of 2-cell embryos had an overall similar probability to arrest at any stage before the blastocyst (2-cell, 4-cell, 8-cell, and morula) or to achieve the blastocyst stage. It was concluded that the localization of maternal mRNAs and proteins at the spindle are evolutionarily conserved between mammals unfertilized ovine oocyte could be considered polar with respect to the spatial regionalization of maternal transcripts and proteins. Even though, the principal forces of this definitive oocyte polarity may not persist during embryonic cleavages.